Controllability of Hilfer Fractional Noninstantaneous Impulsive Differential Inclusions in Banach Spaces - Hammoumi, Ibtissem; Salim, Abdelkrim; Hammouche, Hadda; Benchohra, Mouffak (Фізико-технічний інститут низьких температур ім. Б.І. Вєркіна Національної академії наук України, 2026)
In this paper, we study the existence and controllability of Hilfer fractional differential inclusions with noninstantaneous impulses in Banach spaces. The analysis is conducted using various mathematical tools and the set-valued version of Mönch’s fixed point theorem, which relies on several properties of the Kuratowski measure of noncompactness. To demonstrate the applicability of our results, we conclude the study with a detailed example. Mathematical Subject Classification 2020: 34A08, 34A60, 34H05